FILSAFAT HUKUM, IDEOLOGI DAN MASYARAKAT (Perspektif Marxisme dan Islam) - Humam Balya; Muhammad Said (AL-RASYAD: JURNAL HUKUM DAN ETIKA BISNIS SYARIAH, 2024)
This research digs a comparison of legal philosophical perspectives between Marxism and Islam. The main focus is to analyze the views of both in relation to the concepts of law, justice, and its role in society. In the context of Marxism, the study deals with Marx's views and critical thinking of the capitalist legal system, as well as efforts to create a more just socialist society. On the other hand, it also explores the Islamic view of law, based on principles of Sariah, social justice, and Islamic rule. The study aims to understand the similarities, differences, and potential collaboration between Marxism and Islam in formulating legal solutions relevant to contemporary social and economic challenges. The method of analysis is used as an overview in the analysis and interpretation of key texts related to Marxism and Islam in the context of Marx's legal philosophy and works, other Marxist thought, as well as classical and contemporary texts in Islamic thought, especially those related to law, justice, and government. This paper also uses methods of comparative analysis to compare the legal systems influenced by Marxism and Islam. For example, on the concept of law, justice, and its role in society. The results of the study show that there is a comparison of legal concepts, especially in defining the law, the sources of law, and the purpose of law. Both, can play a role in the formation of the legal system in a State. For example, the principles of Marxism or Islam influence laws, policies, or legal decisions, and there are social and political implications of the application of principles in the context of the law. This could include its impact on political stability, social well-being, or individual rights.